65, 000 years of changing plant food and landscape use at Madjedbebe, Mirarr country, northern Australia. (15th May 2022) - Florin, S. Anna; Fairbairn, Andrew S.; Nango, May; Djandjomerr, Djaykuk; Hua, Quan; Marwick, Ben; Reutens, David C.; Fullagar, Richard; Smith, Mike; Wallis, Lynley A.; Clarkson, Chris
Abstract: The plant macrofossil assemblage from Madjedbebe, Mirarr Country, northern Australia, provides insight into human-plant relationships for the ∼65, 000 years of Aboriginal occupation at the site. Here we show that a diverse diet of fruits, nuts, seeds, palm and underground storage organs was consumed from the earliest occupation, with intensive plant food processing in evidence. The diet varied through time as foraging strategies were altered in response to changes in environment and demography. This included a broadening of the diet during drier glacial stages, as well as changes in the seasonal round and incorporation of new foods with the formation of freshwater wetlands following sea level rise in the late Holocene. The foundations of the economy evidenced at Madjedbebe include seasonal mobility, a broad diet and requisite plant processing and grinding technologies, all of which are maintained throughout the entire timespan of occupation. This points to a resilient economic system in the face of pronounced environmental change. Highlights: Diverse range of plant foods eaten, and intensive plant processing evidenced. Diet broadened with drier glacial stages and increased use of the site. Seasonal round changed and new plant foods used upon formation of wetlands. Vegetation burning likely practised from earliest occupation. Seasonal mobility, broad diet and complex technologies allowed resilience over time.